Pseudosciences: A new threat to the secular humanist project - García-Belaunde Velarde, Víctor (2023)
Historically, secular humanism has been in conflict with religious thought in the academic and social spheres. This article supports the thesis that in modern times pseudosciences and pseudoscientific thinking are a threat to the humanist project, comparable to religious fundamentalism. To prove it, the concept of Secular Humanism and how it is threatened by religious fundamentalism is explained. This is followed by the definition of what pseudosciences are and what pseudoscientific thinking is. Subsequently, the way how pseudosciences threaten the secular humanist project is described. The conclusion states that pseudoscientific thought and religious fundamentalism are equally dangerous for social coexistence.